Adaptive Behavior of Farmers in Cyclone Vulnerable State of India: Global Priorities Weightage Analysis - Mallick, Biswajit; Lal, Sudhanand Prasad; Behera, Bijaylaxmi (International Journal of Bio-resource and Stress Management, 2025)
The ex-post facto study was conducted during (May-July, 2022) at two districts Odisha. Through an ex-post facto study, the study offered actionable insight through the Farmers’ Cyclone Adaptive Capacity Index (FCACI) in Odisha, focusing on 160 respondents across eight villages using the Analytic Hierarchy Process (AHP). Globally, Climate change emerged as a serious issue for human civilizations. It was undoubtedly an unprecedented phenomenon. Variations in weather patterns endanger food production, while the rise of sea levels enhanced the risk of catastrophic events like flooding, cyclones, and storm surges that exacerbate extreme poverty, inequality, and famine in the world. Cyclone was one of the disastrous climatic events in eastern India. Farmers suffered every year due to cyclones and floods in terms of production, and storage of the produce which retard their economic and social growth. Though it costs the life and property of the coastal communities, it was not easy to shift with their land and man so they become adaptable to such vagaries. The concept of adaptive capacity was crucial and needed a careful investigation at micro level. Broad factors such as human-social, economic, environment, and physical responsible for the adaptive capacity of farmers were calculated by using the Analytic Hierarchy Process (AHP), a psycho-mathematical tool for analyzing complex decisions. It was found that ‘Physical’ factor (0.37) was more responsible for adaptive capacity followed by Human-social (0.28), Economic (0.21), and ‘Environment’ factor (0.14) in cyclone affected areas. Community participation and institutional setup like cyclone shelters were crucial for enhancing resilience.